What you're really meant to do : a road map for reaching your unique potential - Kaplan, Robert Steven. (Harvard Business Review Press, 2013)
Presents a roadmap for helping readers define their personal success and reach their potential that covers a critical series of issues that must be addressed in order for them to set and achieve their ultimate goals.